Orbital floor reconstruction planning in the course of silent sinus syndrome using online fab lab – case report - Berczyński, Paweł; Smektała, Tomasz; Oskwarek, Dorota; Dowgierd, Krzysztof; Trybek, Grzegorz; Lewusz, Katarzyna; Sporniak-Tutak, Katarzyna (Journal of Stomatology, 2015)
Silent sinus syndrome is rarely presented in Polish literature. This case report illustrating the deformation of the orbital floor in the course of silent sinus syndrome shows the use of rapid prototyping technology in the planning of orbital floor reconstruction surgery, with particular emphasis on the preparation stage of a virtual model. The starting point was computed tomography imaging. Using open source software, a virtual reconstruction of the orbit was obtained. A model was then produced by means of a laser sintering technique using online Fab Lab (Sculpteo). Prior to surgery, a semi-individual titanium plate was moulded from the prepared form, which was then used as a next step in the reconstruction of a new orbital floor.